An evaluation of the internal audit function from the perspective of external auditors - Lim, Seng Leong (2014)
Statement of Auditing Guideline 11 (SAG 11) “using the Work of an Internal Auditor” provides the guidelines the external auditor should follow in assessing the working of the internal auditor for the purpose of using that work. In particular, paragraph 10 provides four important criteria for conducting a general evaluation of the internal audit function. The four criteria are organisational status, scope of function, technical competence and due professional care.